Mesenteric Lymph Node Transplantation in Mice to Study Immune Responses of the Gastrointestinal Tract - Shaikh, Haroon; Vargas, Juan Gamboa; Mokhtari, Zeinab; Jarick, Katja J.; Ulbrich, Maria; Mosca, Josefina Peña; Viera, Estibaliz Arellano; Graf, Caroline; Le, Duc-Dung; Heinze, Katrin G.; Büttner-Herold, Maike; Rosenwald, Andreas; et al. (Frontiers in Immunology, 2021)
Mesenteric lymph nodes (mLNs) are sentinel sites of enteral immunosurveillance and immune homeostasis. Immune cells from the gastrointestinal tract (GIT) are constantly recruited to the mLNs in steady-state and under inflammatory conditions resulting in the induction of tolerance and immune cells activation, respectively. Surgical dissection and transplantation of lymph nodes (LN) is a technique that has supported seminal work to study LN function and is useful to investigate resident stromal and endothelial cell biology and their cellular interactions in experimental disease models. Here, we provide a detailed protocol of syngeneic mLN transplantation and report assays to analyze effective mLN engraftment in congenic recipients. Transplanted mLNs allow to study T cell activation and proliferation in preclinical mouse models. Donor mLNs proved viable and functional after surgical transplantation and regenerated blood and lymphatic vessels. Immune cells from the host completely colonized the transplanted mLNs within 7-8 weeks after the surgical intervention. Adoptively transferred allogeneic CD4+ T cells from FVB/N (H-2q) mice homed to the transplanted mLNs in C57BL/6 (H-2b) recipients during the initiation phase of acute graft-versus-host disease (aGvHD). These CD4+ T cells retained full proliferative capacity and upregulated effector and gut homing molecules comparable to those in mLNs from unmanipulated wild-type recipients. These data support that orthotopically transplanted mLNs maintain physiological functions after transplantation. The technique of LN transplantation can be applied to study migratory and resident cell compartment interactions in mLNs as well as immune reactions from and to the gut under inflammatory and non-inflammatory conditions.